Decarbonization as a socio-ecological fix - Krommyda, Vasiliki; Gialis, Stelios; Stratigea, Anastasia (The Greek Review of Social Research, 2022)
The article uses the “socio-ecological fix” concept in order to critically analyse contemporary energy transition processes. It discusses the inherent contradictions of such transitions and the need to actively involve local communities in planning the emerging energy geographies. Influenced by Geographical Political Economy and drawing upon three central EU case study regions, the rationale behind decarbonisation policies and their work implications are studied. Furthermore, the ongoing energy transition in Western Macedonia is critically approached, highlighting the excessive risk of job loss and increasing precarity. A key finding is that the emerging “socio-ecological fix” will not lead to a “just transition”.